Sensitivity of European blocking to physical parameters in a large ensemble climate model experiment - Tim Woollings; Marie Drouard; David M. H. Sexton; Carol F. McSweeney (Atmospheric Science Letters)
Abstract The occurrence of blocking weather patterns over Europe is analysed in a large ensemble of simulations of a climate model with perturbed physical parameters. The experiments were performed with HadGEM3‐GC3 for the UK Climate Change Projections, and comprise a set of 15 coupled simulations supported by a larger suite of 505 atmosphere‐only simulations. Despite the systematic perturbation of 47 different physical constants in the atmosphere‐only experiments, only three were found to have any impact on European blocking frequencies. These reveal the sensitivity of European blocking to orographic drag in winter and to convective entrainment in summer. However, these sensitivities cannot be traced through to the coupled simulations, due to the smaller and more realistic range of perturbations used and likely also to coupled dynamical effects. Overall, we find that although physical sensitivity to the parameterisations exists, adjustment of the parameters is no replacement for further structural improvement in the representation of these processes in the model.